EVALUASI TERHADAP NILAI-NILAI UNIVERSAL: Sebuah Aplikasi di Sekolah - BUDININGSIH, C ASRI (FOUNDASIA, 2015)
The basic universal values are necessary in teaching the school students, rot it will become a ,guidance in encountering national, regional as well as international open interaction, Teachers are necessary to understand what is meant by the universal values, how to leach and evuluate them. The universality ojvalues might be meant within the main principles as a core and structure of them. For example, the universal moral values are justice, reciprocity, while the faith, the existential faith is the universal faith, as well as empathy, democratization. etc. The teachers are not only demanded to be able to teach these values. but they also must be able to evaluate how far the development of them within the personalities of the students.